The Trojan Bacillus: Transgenic Bacteria in Cancer Therapy - Thomas, Matthew (Trinity Student Medical Journal, 2022)
A classic conundrum in oncology is the identification of cancer-specific, druggable molecules which can be targeted with minimal systemic toxicity. A novel candidate for administering cancer therapeutics has emerged in bacteria, which may prove to be excellent delivery vehicles for biologics whose systemic delivery causes severe and unacceptable adverse effects. Bacteria are well-suited to this role due to their ability to colonise tumour microenvironments, synthesise drug molecules, and potentiate innate and adaptive immune responses. Genetic clockwork in the form of quorum sensing mechanisms allows these bacteria to lyse on demand, releasing therapeutic payloads into tumours. Recent in vivo evidence outlined here support this hypothesis, yet there is a great deal of research and refinement still to be done.